2018
DOI: 10.1111/eip.12752
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the direct and indirect costs of a first episode of psychosis program: Insights from PAFIP of Cantabria, Spain, during the first year of intervention

Abstract: Aim: Early intervention psychiatric services for patients with psychosis aim to limit the most damaging outcomes and reduce the patient's risk of social drift, decreasing illness severity and thus containing healthcare costs. There is a scarcity of studies that focus on first-episode psychosis (FEP), and those few that have been published only looked at direct health costs, but not at indirect costs, which make up the bulk of the budget.Our study aims to explore the short-term (1-year follow-up) economic cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Moreover, Baumann et al (2013) observed that 8 years after implementation, an EIP program in Lausanne (Switzerland) included 350 young patients (aged 14–25 years) with a disengagement rate of 9% over 3 years of treatment. Finally, Mayoral‐van Son et al (2019) reported that 157 young people with early psychosis (aged 15–25 years) entered a specific EIP program in Cantabria (Spain) during a 1‐year treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Baumann et al (2013) observed that 8 years after implementation, an EIP program in Lausanne (Switzerland) included 350 young patients (aged 14–25 years) with a disengagement rate of 9% over 3 years of treatment. Finally, Mayoral‐van Son et al (2019) reported that 157 young people with early psychosis (aged 15–25 years) entered a specific EIP program in Cantabria (Spain) during a 1‐year treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulating evidence suggests that negative symptoms have more impact on everyday functioning and quality of life than positive and other symptom factors 3 4. Globally, schizophrenia is generally regarded as a low prevalence mental disorder (the global age-standardised point prevalence is 0.28%), but it creates a considerable economic deficit to society due to losses in productivity by individuals, costs for treatment and significant burdens on health and welfare systems 5 6…”
Section: Introductionmentioning
confidence: 99%
“…Failure to achieve remission of symptoms has been associated with the chronicity of the disease and persistent negative symptoms and functional deficits, which are crucial to achieving psychosocial recovery ( Schooler, 2006 ). Chronicity has also been associated with the existence of frequent relapses, a higher burden of principal careers, an impact on direct and indirect costs of the disease, and poorer long-term course outcomes, including those directly associated with the daily psychosocial functioning of patients with an FEP ( Álvarez-Jiménez et al, 2012b ; Mayoral-van Son et al, 2019 ). Hence, functional recovery remains the cornerstone in managing and treating patients with an FEP ( Robinson et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%